ANTIOXIDANT AND ANTIMICROBIAL POTENTIAL OF BLACKBERRY POLYPHENOLIC EXTRACTS: INFLUENCE OF DIFFERENT EXTRACTION TECHNIQUES AND SOLVENTS - Todorović, Ana; Cvetanović Kljakić, Aleksandra; Sknepnek, Aleksandra; Belošević, Spasoje; Salević, Ana; Lević, Steva; Mirković, Milica; Nedović, Viktor (Food and Feed Research, 2025)
Blackberries (Rubus sp.) are considered a good source of bioactive compounds, especially polyphenols. The high antioxidant and antimicrobial activity associated with polyphenols offers the possibility of using blackberry extracts in various food applications. This study investigates the potential of blackberry extracts obtained with various solvents and extraction techniques as a source of natural antioxidants and antimicrobial compounds. Ethanol and two natural deep eutectic solvents (NADES) (N1 − choline chloride:glycerol (1:2) and N2 − choline chloride:lactic acid (1:4)) and three different extraction techniques (maceration, ultrasound-assisted extraction, and microwave-assisted extraction) were applied. The extracts were evaluated in terms of total monomeric anthocyanin content, polymeric color, total polyphenol content, and ferric reducing antioxidant power (FRAP). The antimicrobial potential against two Gram-positive and two Gram-negative bacteria, as well as one yeast, was assessed using agar diffusion and broth microdilution methods. The N2 solvent gave a better yield of bioactives than N1 and ethanol, while the microwave-assisted extraction had the most pronounced effect on the extracts' polyphenol content and color. All samples displayed significantly higher antimicrobial activity than the ethanolic extract, with the generally highest efficacy observed against Gram-positive bacteria. Overall, these preliminary results demonstrate the potential of acidic NADES for the extraction and application of blackberry polyphenols. Future steps should include extraction optimization and food application studies.
Keywords: blackberry; polyphenols; NADES; extraction techniques; antioxidants; antibacterial activity